Les Néandertaliens du talon : technologie lithique et mobilité au Paléolithique moyen dans le Salento (Pouilles, Italie méridionale) - Spinapolice, Enza E. (Archaeopress Publishing Ltd, 2018)
Focusing on the abundant Middle Palaeolithic sites in the Salento region of Southern Italy, this work analyses how Neanderthals used and managed raw materials, through both the procurement and use of the locally available materials and the exploitation of possibly more distant sources.